DESAIN KEMASAN DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) PADA PRODUK SNACK BAR - Kurniawan, Mhd Andry; Juarsa, Rahmadini Payla; Sianturi, Eben Ezer; Hawari, Akmal; Khairumi, Salsabila; Siburian, Gilbert Ernest; Aritonang, Andreas Sahat (SAGU, 2024)
Quality function deployment (QFD) is an effective method for providing solutions to problems because it identifies consumer needs and expectations and their use in the development process. The packaging design of a snack bar product is designed using QFD methodology, with the assistance of house of quality (HOQ). The data from the questionnaire will be collected, analyzed and applied to QFD. This study aims to design packaging designs that meet consumer needs and preferences, especially in the development and design of the latest, most innovative and best snack bar products. By integrating the QFD method, two packaging design proposals were obtained to meet consumers’ needs and desires for snack bar product packaging that meets the criteria of five priority specifications, in which consumers want snack bar packaging to have clear product images and information, intuitive packaging design, convenient and modern packaging appearance, brand representation, and packaging materials that are not easily damaged.